2015
DOI: 10.12707/riv14086
|View full text |Cite
|
Sign up to set email alerts
|

Concept clarification of «delayed surgical recovery» for clinical practice implementation

Abstract: Context: While the concept of "delayed surgical recovery" has a high estimated occurrence in surgical nursing practice, the lack of specificity of critical attributes has interfered with diagnostic accuracy and consequent application in clinical practice. There is thus a need for concept clarification. Objectives: To analyse of the concept of the nursing diagnosis «delayed surgical recovery», using the method of Walker and Avant, 2011. Main topics under analysis: Critical attributes were identified and anteced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 7 publications
(18 reference statements)
0
7
0
4
Order By: Relevance
“…Problems that are often experienced by patients who undergo gastric and colorectal cancer surgery, such as nausea, pain, fatigue and loss of appetite, may cause slower recovery and delays in their return to daily routines and work (Delphino et al, 2015; Kahokehr et al, 2010; McGrath et al, 2017; Santana et al, 2018). Some studies have reported that postponing activities at home or work indicate the interruption of surgical recovery (Norlyk & Harder, 2011; Santana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Problems that are often experienced by patients who undergo gastric and colorectal cancer surgery, such as nausea, pain, fatigue and loss of appetite, may cause slower recovery and delays in their return to daily routines and work (Delphino et al, 2015; Kahokehr et al, 2010; McGrath et al, 2017; Santana et al, 2018). Some studies have reported that postponing activities at home or work indicate the interruption of surgical recovery (Norlyk & Harder, 2011; Santana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Preconceptions of the recovery process based on the surgical procedure might be affected negatively among patients who had undergone gastric or colorectal cancer surgery (Norlyk & Harder, 2011). Patients might think that they are not fully recovered or that they need more time to recover after their discharge (Delphino et al, 2015). This study showed that the intervention and control groups reported mild distress about the problem described as perceiving that more time is needed to recover and that there was a statistically significant difference between the groups at the times T2, T3 and T4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(10) It is also seen that in this taxonomic classification system all diagnostic categories are derived from concepts and present theoretical models or formulations (11) to give meaning to the observations of physiological, psychic, social, religious and spiritual phenomena, going through continuous analyzes according to studies found in the literature. (12)(13)(14)(15)(16)(17)(18)(19) As already mentioned, the conceptual definition of powerlessness (00125) standardized by NANDA-I is "lived experience of lack of control over a situation, including a perception that one's actions do not significantly affect a result." (2) .…”
Section: Discussionmentioning
confidence: 99%